Nearly Sasakian manifolds revisited - Cappelletti-Montano Beniamino (De Gruyter, 2019)
We provide a new, self-contained and more conceptual proof of the result that an almost contact metric manifold of dimension greater than 5 is Sasakian if and only if it is nearly Sasakian.